COMPARATIVE EVALUATION OF ONLINE AND CD-ROM SEARCHES IN A CELL SCIENCE LIBRARY IN INDIA - Ramakrishna, N.V. (Malaysian Journal of Library and Information Science, 1997)
Examines the use of online and CD-ROM databases at the National Centre for Cell Science Library, Pune, India. The technologies of online and CD-ROM are analysed and the day-to-day use of these two technologies presented. Increased online and CD-ROM searches created the need of comparing both the system at preliminary level which provided an integrated view of the information process at the NCCS library for future electronic information services. The findings indicate that requests for online searches remained fairly constant, while demand for CD-ROM searches steadily increased. From an analysis of search data of these two systems, the study concludes that both information systems are complementary to each other.